MODEL MULTIMEDIA INTERAKTIF BERBASIS UNITY UNTUK MENINGKATKAN HASIL BELAJAR IKATAN ION (Universitas Negeri Semarang, 2020)
Chemistry is categorized as a subject that is quite difficult for high school students. To understand chemistry, students must have representational abilities. There is a positive correlation between spatial visual ability and learning outcomes on material that uses the ability of the imagination of objects in space. This capability can be supported by the presence of interactive multimedia. Interactive multimedia is needed as a learning media to improve student understanding of certain materials. The purpose of this study is to analyze the effectiveness of interactive multimedia on ionic bonding material in terms of student learning outcomes. The research design used in this study is one group pretest - posttest design system. The instrument was a learning achievement test sheet that tested on 12 high school students. The results showed that the test of learning outcomes obtained N-gain value with a range of 0.8-1.0 with high score criteria. This result proves that the interactive multimedia ionic bond material is effective in improving student learning outcomes.